2018
DOI: 10.1101/267906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tbx1regulates extracellular matrix-cell interactions in the second heart field

Abstract: Tbx1, a gene involved in DiGeorge syndrome, is required for efficient incorporation of cardiac progenitors (CPs) of the second heart field (SHF) into the heart. However, the mechanisms by which TBX1 regulates this process are still unclear. Here, we have used two independent models, in vivo and in vitro, to define the role of TBX1 in establishing morphological and dynamic characteristics of target cells in the mouse. We found that loss of TBX1 impairs cell migration and adhesion in vitro and affects the axis e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…The effects of TBX1 in cell movement have been reported in multiple cell types, including in the cardiopharyngeal mesoderm. [35][36][37] These effects could also explain an impairment of LEC progenitor ontogeny, as they are also found in the cardiopharyngeal/pharyngeal mesoderm, 3,25 as we have shown here.…”
Section: Tbx1 Is Activated and Required During The Early Phases Of supporting
confidence: 83%
See 1 more Smart Citation
“…The effects of TBX1 in cell movement have been reported in multiple cell types, including in the cardiopharyngeal mesoderm. [35][36][37] These effects could also explain an impairment of LEC progenitor ontogeny, as they are also found in the cardiopharyngeal/pharyngeal mesoderm, 3,25 as we have shown here.…”
Section: Tbx1 Is Activated and Required During The Early Phases Of supporting
confidence: 83%
“…Other mechanisms may be in place, for example, through cell-to-extracellular matrix signaling pathways, which are altered in Tbx1 mutants. 35…”
Section: Tbx1 Is Activated and Required During The Early Phases Of mentioning
confidence: 99%
“…Modulation of the extracellular microenvironment within the pharynx is essential for the development cardiovascular system 29,31,59,63,64,[71][72][73][74][75][76][77][78][79][80][81] . The expression of Fn1, an essential ECM glycoprotein, is highly enriched in the pharyngeal epithelia 28,29 , and our studies show that signaling by Fn1 in the Isl1 lineages is important for the accrual of SHF-derived cells to the pharyngeal mesenchyme, and for the formation of the 4 th PAAs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using Tbx1 +/mice that model 22q11 deletion syndrome indicated that defective formation of the left 4 th PAA underlies IAA-B in these patients 65,86,87 . Intriguingly, several independent publications demonstrated that Tbx1 regulates the expression of integrins and extracellular matrix (ECM) components, and showed that defects in cell-ECM interactions downstream of Tbx1 precede pathological sequelae and cardiovascular defects in Tbx1 mutants [71][72][73] . Interestingly, about 50% of Tbx1 +/mice recover from the initial defect in PAA formation, and are viable and fertile 50 ; However, this recovery can be impeded by the reduction in the expression of Fn1 .…”
Section: Discussionmentioning
confidence: 99%
“…1, asterisks). Examples of cell recruitment have been reported in both vertebrate and invertebrate development such as in the Drosophila wing (Baéna-López and García-Bellido, 2003;Zecca and Struhl, 2007a;Zecca and Struhl, 2010), as well as in the vertebrate inner ear (Morrison et al, 1999;Kiernan et al, 2005;Kiernan et al, 2006), thyroid (Fagman et al, 2006;Lania et al, 2009), kidney (Lindström et al, 2018), and heart (Alfano et al, 2019). However, several questions about the molecular and mechanistic aspects of cell recruitment remain open in each of these systems.…”
mentioning
confidence: 99%